A design algorithm for an electric power system using wide-area interconnection of renewable energy. (15th February 2020) - Okada, Masaki; Onishi, Terumi; Obara, Shin'ya
Abstract: This study aims to study the utilization factor of an electricity transmission network by determining the optimal installation of renewable energy technologies and heat pumps that store heat. The proposed model considers the electricity demand, heat load, and meteorological data with respect to each area of the transmission network and selects the type and capacity of renewable electricity sources in each area as well as the capacity of the required compensation electricity supply. The heat input and output of heat equipment and the amount of power supply of the transmission line were decided as each energy balance equilibrating. Therefore, an analysis method that uses genetic algorithm was introduced to achieve optimal operation planning. The proposed methodology is applied to the existing electric system in the island of Hokkaido, Japan, as a case study. Optimization of the arrangement and capacity of renewable electricity generation and transmission network increased the share of renewable energy from 11% to 33.8%. Furthermore, the transmission line utilization factor of the present transmission network improved from 14.5% to 41% when the installation location and capacity of renewable energy were optimized using the proposed methodology. Highlights: System modeling of existing electricity transmission network. Design of placement and capacity of electricity generation equipment was developed. Installation location, type, and capacity of each renewable energy was optimized. Example of the electric power system of Hokkaido in Japan was studied.